Wednesday

April 23, 2014

April 23, 2014

Posted by **Margie** on Friday, June 29, 2007 at 4:58pm.

Problem: m+9/(m+3)-(-4m-6)/(m+3)

Choices:

a.5 b.-3 c.-3(m-1)/(m+3) d.m-1/m+3

What I Think: I think it is letter d.

(m+9)/(m+3)-(-4m-6)/(m+3)

= (5m+15)/(m+3)

=5(m+3)/(m+3) = ?

Your answer is not correct

**Related Questions**

Math - How would you find the value of m in this problem? 4m + 2 = -2 + 4m Well...

mat?h - What would the answer be to 4m+(-3n)+n? -3n squared +4m 4m+(-3n)+n = 4m...

math 115 CH 7 - A tree casts a shadow that measures 5 m. At the same time, a ...

algebra - can you simplify Simplify 5m - 13n - n + 4m

math - Simplify and solve this equation: 4m + 9 + 5m - 12=42

math - i am trying to simplify this equation 4m+9+5m-12=42

algebra - Simplify 5m - 13n - n + 4m.

Math - Is this right? Simplify by removing factors of 1. 2m^2+2m/10m^2+4m My ...

math - 4m+9+5m-12= 42 my question is how to get m=5 (the answer) can u show me ...

math b - i want to know if this is correct expand the following without using ...